2021
DOI: 10.1186/s12935-021-02008-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic signature composed of transcription factors accurately predicts the prognosis of gastric cancer patients

Abstract: Background Transcription factors (TFs) are involved in important molecular biological processes of tumor cells and play an essential role in the occurrence and development of gastric cancer (GC). Methods Combined The Cancer Genome Atlas Program and Genotype-Tissue Expression database to extract the expression of TFs in GC, analyzed the differences, and weighted gene co-expression network analysis to extract TFs related to GC. The cohort including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…We also analyzed ELK3 mRNA level and protein level with five gastric cancer cell lines ( Figure 1 B,C). From these analyses and a previous report [ 24 ], we selected gastric cancer cell lines exhibiting a relatively low and high expression of the ELK3 gene (SNU484 and SNU638 cells, respectively) and further examined the molecular link between ELK3 and cell migration.…”
Section: Resultsmentioning
confidence: 99%
“…We also analyzed ELK3 mRNA level and protein level with five gastric cancer cell lines ( Figure 1 B,C). From these analyses and a previous report [ 24 ], we selected gastric cancer cell lines exhibiting a relatively low and high expression of the ELK3 gene (SNU484 and SNU638 cells, respectively) and further examined the molecular link between ELK3 and cell migration.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we found that ELK3 was co-overexpressed with circ_0000144 in ovarian cancer cells. ELK3 has been reported to participate in cancer genesis and development, including gastric [ 29 ], breast [ 17 ], and liver cancers [ 30 ]. Although previous studies have also demonstrated that ELK3 expression is altered in ovarian cancer cell lines and tumors through overexpression of miR-378 [ 19 ], the regulatory mechanism by which ELK3 regulates ovarian cancer remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, among the putative promoter elements, we mapped transcription factors associated with EMT in physiology and oncogenesis, such as RFX1 (Isaac et al, 2021), BCL6 (Yang et al, 2020), GLI1 (Lei et al, 2022), and OCT1 (Li et al, 2015). Another AMBN promoter analysis (Smith et al, 2020) identified SP6, later suggested to be among the genes implicated in gastric cancer (Zhou et al, 2021) together with MEF2, which resulted from our own AMBN promoter analysis. Our own recent data have associated AMBN expression levels with testicular (Geng et al, 2022) and ovarian cancer (Geng et al, 2023).…”
Section: Ambn Promoter: Old Insights and New Routesmentioning
confidence: 92%